엑셀을 이용한 SW 비전공자 대상 컴퓨팅 교육 모형 설계 및 효과 분석 - 박윤수(Yoon-Soo Park); 이민정(Minjeong Lee); 이수진(Su-Jin Lee) (디지털콘텐츠학회논문지, 2019)
4차 산업 혁명은 학문 간의 경계를 없애고 정보통신기술(ICT)은 사회 전반에 걸쳐 영향을 미치고 있다. 이에 SW교육이 다양한 전공에서 컴퓨팅 기술 기반의 이해력 융합학문으로서 요구되고 있다. 이에 SW 전공자뿐만 아니라 비전공자에게도 ICT 교육의 중요성에 대한 인식이 변화하고 있다. ICT 교육의 핵심은 컴퓨팅 사고에 기반한 소프트웨어 교육에 있다. 컴퓨팅 사고 학습도구로서 스크래치, 파이썬, 랩터, 엑셀 등 다양한 프로그래밍 언어가 있고 이를 이용한 교육 모형이 있다. 본 연구에서는 기존에 제안되었던 엑셀 기반 컴퓨팅 사고 교육 모형을 정보, 패턴 인식, 알고리즘에 중점을 둔 교육으로 재편하고, SW 비전공자를 대상으로 교육을 진행하였다. 컴퓨팅 사고 역량을 측정하기 위해 학습 이전과 이후 테스트를 진행하여 통계적으로 유의미한 결과를 통해 본 연구에서 제안하는 교육 모형의 효과성을 입증하였다. 따라서 본 연구를 통해 SW 비전공자를 포함한 누구나 엑셀과 같은 ICT 활용 도구로도 컴퓨팅 교육을 효과적으로 접할 수 있다는 것을 입증했으며, 나아가 본 연구가 컴퓨팅 교육용 학습 도구를 확대해 가는데 기여할 것으로 기대한다. With the advent of Industry 4.0, the discipline of Information and Communication Technology (ICT) has the potential to affect all aspects of society. Accordingly, understanding of computing technology is required as a convergence study in various majors. Therefore, the importance of ICT education is emphasized not only for SW major but also non-major. The core of ICT education is SW education based on computational thinking(CT). As a CT learning tool, there are various programming languages such as Scratch, Python, Raptor and Excel. In this study, the previously proposed Excel-based CT education model was revised into focusing on information, pattern recognition, and algorithm, and education was conducted for SW non-majors. Tests were administered before and after learning to measure CT ability and the effectiveness of the proposed education model was proved through statistically significant test results. This study showed that anyone including SW non-majors can achieve CT education effectively using Excel. It is expected that this study will contribute to expanding learning tools for computing education. KCI Citation Count: 8